2014
DOI: 10.1177/000313481408000715
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Drainage of a Diverticular Abscess Should be Limited to Two Attempts for a Resilient Diverticular Abscess

Abstract: Management of a resilient diverticular abscess poses a big challenge. Currently there are no guidelines for the number of percutaneous drainages to be performed in resilient diverticular abscesses before attempting surgery. All patients (n = 117) who presented with a computed tomography scan-proven diverticular abscess from July 2008 to June 2011 were studied. They were divided into four groups based on the number of percutaneous drainages they underwent for their diverticular abscess: six patients underwent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
2
1
7
Order By: Relevance
“…Of the patients who recurred, most patients could repeatedly be treated with antibiotics or percutaneous drainage and only four out of 21 with recurrent abscesses required surgery. No patients needed more than two episodes of percutaneous intervention and it has been suggested that percutaneous drainage should be limited to two attempts before surgery . Pelvic abscesses (Hinchey II) were more commonly handled by percutaneous drainage than mesocolic and pericolic abscesses in our series, without being more prone to recur in contrast with the findings of Ambrossetti et al .…”
Section: Discussioncontrasting
confidence: 61%
“…Of the patients who recurred, most patients could repeatedly be treated with antibiotics or percutaneous drainage and only four out of 21 with recurrent abscesses required surgery. No patients needed more than two episodes of percutaneous intervention and it has been suggested that percutaneous drainage should be limited to two attempts before surgery . Pelvic abscesses (Hinchey II) were more commonly handled by percutaneous drainage than mesocolic and pericolic abscesses in our series, without being more prone to recur in contrast with the findings of Ambrossetti et al .…”
Section: Discussioncontrasting
confidence: 61%
“…Se recomienda realizar un máximo de dos intentos de drenaje percutáneo antes de realizar una cirugía definitiva (108) . La perforación diverticular (Hinchey III y IV) se desarrolla casi exclusivamente en el primer episodio de diverticulitis, y generalmente no se desarrolla en pacientes con múltiples episodios (99) .…”
Section: Enfermedad Diverticular Complicadaunclassified
“…Encontramos resultados similares a los publicados por Álvarez (31) , Costi (140) y Ünlü (86) , que describieron menos de un 2% de DPC. Otros estudios, como los de Kaiser (82) , West (106) , y Kotzampassakis (130) , informan menos del 10% de DPC, mientras que Brandt (79) en su estudio comparando el drenaje percutáneo guiado por TAC con el tratamiento antibiótico en los pacientes con diverticulitis Hinchey II, Mäkelä (103) en su artículo sobre el abanico y los resultados de la enfermedad diverticular, Lahat (127) en su publicación sobre diverticulitis en pacientes jóvenes, Mueller (117) en su estudio sobre resultados postoperatorios y comorbilidad en los pacientes con diverticulitis perforada, Gaertner (172) en su artículo sobre el drenaje percutáneo de los abscesos en la diverticulitis aguda y la necesidad de resección del colon, Subhas (108) en su publicación sobre el número de intentos de drenajes de absceso diverticulares a través de un drenaje percutáneo, y Elagili (173) en su estudio sobre la evaluación de los resultados del drenaje percutáneo sin cirugía en pacientes con absceso diverticular, refieren hasta un 93% de DPC. Esta diferencia con respecto al porcentaje, se debe al diseño del estudio, donde el DPC, es el motivo del mismo.…”
Section: Abordaje Laparoscópicounclassified
See 2 more Smart Citations